An algebra problem by Efren Medallo

Algebra Level 5

Let f ( x ) = x 3 \mathrm{f}(x) = \sqrt[3]{x} defined over R \mathbb{R} .

If f ( f ( 2 ) 1 ) = f ( a ) f ( b ) + f ( c ) \mathrm{f}( \mathrm{f}(2) - 1) = \mathrm{f}(a) - \mathrm{f}(b) + \mathrm{f}(c) for positive rational numbers a > b > c a>b>c , and that a + b + c = P Q a+b+c = \frac{ P}{Q} for coprime positive integers P P and Q Q , determine P + Q P+Q .


The answer is 16.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Efren Medallo
Jun 4, 2017

Remember, m 3 ± n 3 = ( m ± n ) ( m 2 m n + n 2 ) \color{#3D99F6} m^3 \pm n^3 = (m \pm n)(m^2 \mp mn + n^2) \color{#333333} .

S = f ( f ( 2 ) 1 ) = 2 3 1 3 S = \mathrm{f}(\mathrm{f}(2) -1) = \sqrt[3]{\sqrt[3]{2} - 1}

S = ( 2 3 1 ) 2 3 2 + 2 3 + 1 2 3 2 + 2 3 + 1 3 S = \sqrt[3]{ (\sqrt[3]{2} - 1) \cdot \frac{ \sqrt[3]{2}^2 + \sqrt[3]{2} + 1}{\sqrt[3]{2}^2 + \sqrt[3]{2} + 1}}

S = 2 1 2 3 2 + 2 3 + 1 3 S = \sqrt[3]{\frac{2-1}{\sqrt[3]{2}^2 + \sqrt[3]{2} + 1}}

S = 1 2 3 2 + 2 3 + 1 3 S = \sqrt[3]{\frac{1}{\sqrt[3]{2}^2 + \sqrt[3]{2} + 1}}

S = 3 3 ( 2 3 2 + 2 3 + 1 ) 3 S = \sqrt[3]{\frac{3}{3(\sqrt[3]{2}^2 + \sqrt[3]{2} + 1)}}

S = 3 ( 2 + 1 ) ( 2 3 2 + 2 3 + 1 ) 3 S = \sqrt[3]{\frac{3}{(2+1)(\sqrt[3]{2}^2 + \sqrt[3]{2} + 1)}}

S = 3 ( 2 3 + 1 ) ( 2 3 2 2 3 + 1 ) ( 2 3 2 + 2 3 + 1 ) 3 S = \sqrt[3]{\frac{3}{(\sqrt[3]{2}+1)(\sqrt[3]{2}^2 - \sqrt[3]{2} + 1)(\sqrt[3]{2}^2 + \sqrt[3]{2} + 1)}}

S = 3 ( 2 3 + 1 ) ( 2 3 4 + 2 3 2 + 1 ) 3 S = \sqrt[3]{\frac{3}{(\sqrt[3]{2}+1)(\sqrt[3]{2}^4 + \sqrt[3]{2}^2 + 1)}}

S = 3 ( 2 3 + 1 ) ( 2 2 3 + 2 3 2 + 1 ) 3 S = \sqrt[3]{\frac{3}{(\sqrt[3]{2}+1)(2 \sqrt[3]{2} + \sqrt[3]{2}^2 + 1)}}

S = 3 ( 2 3 + 1 ) ( 2 3 2 + 2 2 3 + 1 ) 3 S = \sqrt[3]{\frac{3}{(\sqrt[3]{2}+1)( \sqrt[3]{2}^2 + 2 \sqrt[3]{2} + 1)}}

S = 3 ( 2 3 + 1 ) ( 2 3 + 1 ) 2 3 S = \sqrt[3]{\frac{3}{(\sqrt[3]{2}+1)(\sqrt[3]{2} + 1)^2 }}

S = 3 ( 2 3 + 1 ) 3 3 S = \sqrt[3]{\frac{3}{(\sqrt[3]{2}+1)^3}}

S = 3 3 2 3 + 1 S = \frac{ \sqrt[3]{3} }{ \sqrt[3]{2} + 1}

S = 3 3 3 2 ( 2 3 + 1 ) S = \frac{ 3}{ \sqrt[3]{3}^2 ( \sqrt[3]{2} + 1) }

S = 2 + 1 9 3 ( 2 3 + 1 ) S = \frac{2+1}{ \sqrt[3]{9} ( \sqrt[3]{2} + 1) }

S = ( 2 3 + 1 ) ( 2 3 2 2 3 + 1 ) 9 3 ( 2 3 + 1 ) S = \frac{(\sqrt[3]{2} + 1)(\sqrt[3]{2}^2 -\sqrt[3]{2} + 1)}{ \sqrt[3]{9} ( \sqrt[3]{2} + 1) }

S = 2 3 2 2 3 + 1 9 3 S = \frac{\sqrt[3]{2}^2 - \sqrt[3]{2} + 1}{\sqrt[3]{9}}

S = 4 9 3 2 9 3 + 1 9 3 S = \sqrt[3]{ \frac{4}{9}} - \sqrt[3]{ \frac{2}{9}} + \sqrt[3]{ \frac{1}{9}}

S = f ( a ) f ( b ) + f ( c ) S = \mathrm{f}(a) - \mathrm{f}(b) + \mathrm{f}(c)

a + b + c = 7 9 a + b + c = \frac{7}{9}

P + Q = 16 P+Q= 16

Such an epic solution!

Kelvin Hong - 4 years ago

Log in to reply

Thanks! :)

Efren Medallo - 4 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...